2009
DOI: 10.1007/s00221-009-1836-z
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilesional trajectory control is related to contralesional arm paralysis after left hemisphere damage

Abstract: We have recently shown ipsilateral dynamic deWcits in trajectory control are present in left hemisphere damaged (LHD) patients with paresis, as evidenced by impaired modulation of torque amplitude as response amplitude increases. The purpose of the current study is to determine if these ipsilateral deWcits are more common with contralateral hemiparesis and greater damage to the motor system, as evidenced by structural imaging. Three groups of right-handed subjects (healthy controls, LHD stroke patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 40 publications
(54 reference statements)
8
31
0
Order By: Relevance
“…This hypothesis is consistent with lesion studies that have shown that right and left hemisphere lesions produce different motor control deficits in the ipsilesional arm of stroke survivors (Hermsdorfer et al, 1999a, Hermsdorfer et al, 1999b, Haaland et al, 2004, Yarosh et al, 2004, Wetter et al, 2005, Schaefer et al, 2007, Chestnut and Haaland, 2008, Haaland et al, 2009, Poole et al, 2009, Schaefer et al, 2009b, a). However, it is also plausible that each hemisphere mediates similar control mechanisms, but that each hemisphere has become more practiced in one or the other mode of control, leading to different control strategies under naïve conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis is consistent with lesion studies that have shown that right and left hemisphere lesions produce different motor control deficits in the ipsilesional arm of stroke survivors (Hermsdorfer et al, 1999a, Hermsdorfer et al, 1999b, Haaland et al, 2004, Yarosh et al, 2004, Wetter et al, 2005, Schaefer et al, 2007, Chestnut and Haaland, 2008, Haaland et al, 2009, Poole et al, 2009, Schaefer et al, 2009b, a). However, it is also plausible that each hemisphere mediates similar control mechanisms, but that each hemisphere has become more practiced in one or the other mode of control, leading to different control strategies under naïve conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with middle cerebral artery lesions, this would refer to the non-paretic arm. In fact, ipsilesional arm motor deficits have been reported in the literature as early as 1967 (Wyke, 1967), and the hemisphere-specificity of these deficits was revealed over many studies and laboratories using detailed kinematic and kinetic analysis (Hermsdorfer et al, 1999a, Hermsdorfer et al, 1999b, Haaland et al, 2004, Yarosh et al, 2004, Wetter et al, 2005, Schaefer et al, 2007, Chestnut and Haaland, 2008, Haaland et al, 2009, Poole et al, 2009, Schaefer et al, 2009b, a). The laboratories of Winstein (Pohl et al, 1996, Pohl and Winstein, 1999, Winstein et al, 1999, Stewart et al, 2014b, a) and Haaland (Haaland and Harrington, 1989, Harrington and Haaland, 1991, Haaland and Harrington, 1994, 1996) corroborated findings that left-hemisphere lesions produce deficits in the early acceleration phase of motion, but not in the late deceleration phase.…”
Section: Discussionmentioning
confidence: 99%
“…Note that simple movements are usually less impaired in stroke and that increasing task demands lead to increased ipsilateral motor control . The current approach was further supported by previous findings showing that lesions of the motor-dominant, left hemisphere have been associated with ipsilesional deficits of gross manual dexterity (Desrosiers et al, 1996), force scaling (Colebatch and Gandevia, 1989;, static arm position (Wyke, 1966), rapid uni-and bilateral arm movements (Wyke, 1967, Wyke, 1971a, 1971b, pursuit rotor tracking (Wyke, 1968), movement sequencing (Jason, 1985;Rosenbaum, 1991), and -most importantly for the current study -reach-to-grasp movements (Haaland et al, 2009;Hermsdörfer et al, 1999). These findings have been interpreted as evidence that LHS may produce a global sensorimotor dysfunction of both hands (Nowak et al, 2007a;Schaefer et al, 2012).…”
Section: Introductionsupporting
confidence: 73%
“…Damage to the left hemisphere in right-handed stroke patients produces deficits in intersegmental coordination in the ipsilesional arm, that is, the arm on the same side as the stroke that is often thought of as intact with respect to motor control. In contrast, damage to the right hemisphere produces deficits in control of stable limb position, or limb impedance (Haaland et al 2009;Schaefer et al 2007). A recent study showed that these differences are amplified when patients adapt to novel visuomotor rotations.…”
Section: Discussionmentioning
confidence: 90%
“…This model has recently been supported by a series of studies in the ipsilesional arm of stroke patients (Haaland et al 2009;Schaefer et al 2007Schaefer et al , 2009a. Damage to the left hemisphere in right-handed stroke patients produces deficits in intersegmental coordination in the ipsilesional arm, that is, the arm on the same side as the stroke that is often thought of as intact with respect to motor control.…”
Section: Discussionmentioning
confidence: 96%